Acute high fat diet consumption activates the mesolimbic circuit and requires orexin signaling in a mouse model. - Spring Valdivia (PLoS ONE, 2014)
Overconsumption of palatable energy-dense foods has negative health implications and it is associated with obesity and several eating disorders. Currently, little is known about the neuronal circuitries activated by the acute ingestion of a rewarding stimulus. Here, we used a combination of immunohistochemistry, pharmacology and neuronal tracing analyses to examine the role of the mesolimbic system in general, and the orexin neurons in particular, in a simple experimental test in which naïve mice are allowed to spontaneously eat a pellet of a high fat diet (HFD) for 2 h. We found that acute HFD activates c-Fos expression in several reward-related brain areas, including the ventral tegmental area (VTA), nucleus accumbens, central amygdala and lateral hypothalamic area. We also found that: i- HFD-mediated orosensory stimulation was required for the mesolimbic pathway activation, ii- acute HFD differentially activates dopamine neurons of the paranigral, parabrachial pigmented and interfascicular sub-regions of the VTA, and iii- orexin neurons of the lateral hypothalamic area are responsive to acute HFD. Moreover, orexin signaling blockade, with the orexin 1 receptor antagonist SB-334867, reduces acute HFD consumption and c-Fos induction in the VTA but not in the other mesolimbic nuclei under study. Finally, we found that most orexin neurons responsive to acute HFD innervate the VTA. Our results show that acute HFD consumption recruits the mesolimbic system and that the full manifestation of this eating behavior requires the activation of orexin signaling.